Gene expression of endothelin receptors in replaced rheumatic mitral stenotic valves - Leão,Sydney Correia (2012)
OBJECTIVES: Rheumatic fever is a highly prevalent disease in Brazil, and it poses a major public health problem. It is the leading cause of acquired heart disease in childhood and adolescence. The aim of this study was to evaluate the gene expression of ET-3 and its receptors, in replaced rheumatic mitral valves. METHODS: We studied the gene expression of endothelin-3 (ET-3) and its receptors, endothelin receptor A and endothelin receptor B (ETr-A and ETr-B), in the rheumatic mitral valves of 17 patients who underwent valve replacement surgery. The samples also underwent a histological analysis. RESULTS: Our data showed that almost all patients, regardless of individual characteristics such as gender or age, expressed the endothelin receptor genes, but did not express the genes for ET-3. In quantitative analysis, the ETr-A/GAPDH mean ratio was 33.04 ± 18.09%; while the ETr-B/GAPDH mean ratio was 114.58 ± 42.30%. Regarding histopathological individual features, the frequency of fibrosis is 100%, 88.23% of mononuclear infiltrate, 52.94% of neovascularization, 58.82% of calcification and absence of ossification. CONCLUSION: The presence of receptors ETr-A and ETr-B in rheumatic mitral valves suggests its interaction with the system of circulating endothelins, particularly ETr-B (known for acting in the removal of excess endothelin) detected in a greater proportion, which could explain the lack of expression of endothelin in rheumatic mitral valve, process to be elucidated.